ENHANCING STUDENTS’ COMPOSITIONAL THINKING THROUGH INNOVATIVE TECHNOLOGIES - Jalolov Shavkat Choriyevich (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2025)
Abstract: This article examines the effectiveness of innovative pedagogical technologies in developing students’ compositional thinking in art education. Methods such as flipped classroom, project-based learning, interactive digital platforms, and virtual design tools are analyzed for their role in enhancing students’ creative potential and artistic competencies. The study draws on the research of Shovdirov S.A. and other scholars to highlight the methodological and pedagogical aspects of applying innovative technologies in modern art education.